ANALISIS OPTIMASI KEBUTUHAN DAYA LISTRIK PADA KAPAL PENUMPANG RO-RO KM. EGON DENGAN METODE DYNAMIC PROGRAMMING - Alexius Bayu Setyoko; Eko Sasmito Hadi; Untung Budiarto (Jurnal Teknik Perkapalan, 2013)
KM. Egon is a passenger ship which is of the same type of Ro-Ro owned by PT. Pelayaran Nasional Indonesia (PELNI). This ship has two diesel generators and shaft generators. To produce enough power needed by the load, the four generators in KM. Egon should be able to operate efficiently. However, the arrangement of the load was less efficient so the use of fuel was wasteful. In this study, the researcher did several steps. First, calculating the capacity of the equipments was by counting the load factor value of the equipments. Second, finding out the number of the load in every operational condition of the ship, at port, maneuver, and shipping out. Third, finding out the load factor of the generator of the variation of the generator which was used with used the simulation of the dynamic programming method in order to get load which used the fuel efficiently. The calculation result of the number of the load in every condition for in port was 219.84 kW, then maneuver was 1014.37 kW, and shipping out was 419.55 kW. The dynamic programming method which was applied for KM. Egon ship in the simulation from Semarang to Kumai then  went back to Semarang. The efficient fuel consumption was in port or anchoring 41.43 liter/hour. It used diesel generator 1 or diesel generator 2. Then maneuver and shipping out was 27.90 liter/hour by operating one diesel generator and one shaft generator. Therefore, the total use of  fuel of auxiliary engine  in the simulation was 2622.42 liter.